Assessment of Health-Related Quality of Life Using EuroQoL-5 Dimension in Populations With Prediabetes, Diabetes, and Normal Glycemic Levels in Southwest China - Long, Enwu; Feng, Shuang; Zhou, Li; Chen, Jie; Shi, Lizheng; Jiang, Xuehua; Hu, Ming; Yang, Nan (Frontiers in Public Health, 2021)
Objectives: The aim of this study was to describe and compare health-related quality of life（HRQoL）among populations with normal glycemic levels, pre-diabetes and diabetes in southwest China and to offer baseline data that can be easily compared other regions in China or across countries. Methods: A quality of life survey based on the EuroQoL-5 Dimension-5 level scale was conducted through face-to-face or telephone interviews. A total of 403 respondents with diabetes, 404 with prediabetes, and 398 with normal blood glucose were enrolled in the survey. Propensity score matching was used to decrease the bias of three groups, conditional on age, gender, BMI, and household income. For there were 3 groups, we matched two groups first, and then matched the result with the third group. Differences among groups were compared by chi-square test one-way analysis of variance after adjusting by PSM. Results: In general, the blood glucose of people with diabetes was generally well controlled in southwest China, but they were often accompanied by circulatory system and nutritional metabolic diseases. 99 individuals from each group were matched. The EuroQoL-5 Dimension index of population with normal glycaemic levels, prediabetes, and diabetes patients was 0.901, 0.948, and 0.897. The EuroQol-visual analogue scales (scores of each group above were 73.76, 77.45, and 68.34. HRQoL in males were higher than that of females in the three study groups. The results after propensity score matching were consistent with that before matching。 Conclusion: There was a general trend that patients were associated with a decline of HRQoL from prediabetic population, population with normal glycaemic levels to diabetic population . Pain/discomfort and anxiety/depression might not be specific for population with or without diabetes.